The capital gain and its impact on public finances (2016)
The capital Gain has been settled down as an instrument of management of the land use planning from institutions territorial entities this is enjoy at urban development with different resources that can generate construction of housings with social interest also public works. In this report I am going to explain how the charge of the tax and which is his destination, therefore it show the impact to publics finances even so is a tax settled in the law 388 of 1997, in many states the tax is not charge causing a deficit in earnings with specific destination, this document want to mark out the important of charge tax his possible advantage and benefits for the society.